SPEECH AND LANGUAGE DISORDER ON KING GEORGE VI IN THE KING’S SPEECH - Nurnisa, Sofia; Damanhuri, Adam (Language Horizon: Journal of Language Studies, 2022)
This research aims to locate the causes of King George VI’s speech and language disorder in The King’s Speech and how he copes with it. Speech disorders refer to a communication issue and the related areas such as oral motor function and anticipatory anxiety. The movie depicts the story of King George who suffered from stuttering leaving him with speech disorder since childhood. This study uses a qualitative descriptive method, which observes the data of behaviors and events, and is presented through narrative description. The data is examined using Nathan Lavid’s and Wendy Leiner’s theories on speech and language disorder. Lavid stated that stuttering comes into a few types: developmental stuttering and stuttering due to diseases such as stroke, and temporary stuttering caused by a sprained tongue due to surprise or panic. Leiner explained that people with stuttering can receive several rare therapies to reduce or even eliminate their stuttering. This research employs a descriptive qualitative method using Nathan Lavid’s and Wendy Leiner’s theories. The result shows that King Goerge VI had been suffering from developmental stuttering, anticipatory anxiety, and brain plasticity. To overcome these disorders, King George VI underwent auditory masking, singing, and speaking alone. It was found that the flow of speech is unconsciously cut off by repeating and prolonging sounds, syllables, words, or phrases, and the failure to produce sound by an unknowing pause. To fix it, King George VI underwent speech therapy, Brain Plasticity and Maneuvers treatments.